2021
DOI: 10.1172/jci.insight.144046
|View full text |Cite
|
Sign up to set email alerts
|

Vagal gut-brain signaling mediates amygdaloid plasticity, affect, and pain in a functional dyspepsia model

Abstract: Functional dyspepsia (FD) is associated with chronic gastrointestinal distress and with anxiety and depression. Here, we hypothesized that aberrant gastric signals, transmitted by the vagus nerve, may alter key brain regions modulating affective and pain behavior. Using a previously validated rat model of FD characterized by gastric hypersensitivity, depression-like behavior, and anxiety-like behavior, we found that vagal activity — in response to gastric distention — was increased in FD rats. The FD phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 72 publications
3
21
0
Order By: Relevance
“…It plays a role in the cross-talk between the brain and gut microbiota and delivers messages to the brain regarding the gut microbiota and related metabolites. Moreover, factors such as stress, inhibit the vagus nerve to potentiate gut inflammation and decrease intestinal permeability, possibly contributing to the modulation of the gut microbiota [ 11 ]. Therefore, suppressing the cholinergic nerve system can contribute to memory dysfunction and inflammatory bowel disease by modulating the microbiota-gut-brain axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It plays a role in the cross-talk between the brain and gut microbiota and delivers messages to the brain regarding the gut microbiota and related metabolites. Moreover, factors such as stress, inhibit the vagus nerve to potentiate gut inflammation and decrease intestinal permeability, possibly contributing to the modulation of the gut microbiota [ 11 ]. Therefore, suppressing the cholinergic nerve system can contribute to memory dysfunction and inflammatory bowel disease by modulating the microbiota-gut-brain axis.…”
Section: Discussionmentioning
confidence: 99%
“…Vagus nerve activation inhibits the peripheral inflammation and decreases the intestinal permeability. By contrast, stress suppresses the vagus nerve, modulates the gut microbiota, and is involved in the pathophysiology of gastrointestinal disorders through inflammatory processes [ 11 ]. Therefore, the vagus nerve acts as the bidirectional modulator of the brain-gut axis in patients with AD and other inflammatory conditions and may be associated with modulating the composition of the gut microbiota to dysbiosis or eubiosis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The principles of treatment with a better biopsychosocial understanding of the gut–brain axis have been highlighted ( 2 ). A recent study reported that the vagal gut-brain signaling regulates both the cerebral pain perception and the structural plasticity of FD in a “bottom-up” manner ( 3 ); however, this may not have a high clinical translational potential. Clinical data have confirmed that duodenal barrier disruption does exist in the patients with FD ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Abundant evidence indicates a subset (∼30%) of functional dyspepsia patients have impaired vagal efferent activity (Hausken et al, 1993;Hveem et al, 1998;Lorena et al, 2002;Dal et al, 2014;Guo et al, 2018). In addition, recent findings, using animal models of functional dyspepsia, suggest vagal afferent signaling in response to gastric distension may be increased in functional dyspepsia (Li et al, 2019;Cordner et al, 2021). Furthermore, vagal nerve stimulation has been shown to reverse some of the pathophysiological changes (Hou et al, 2020;Zhu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%